KARAKTERISTIK DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENGEMBANGAN POTENSI LOKAL PADA WILAYAH PERI-URBAN (WPU) KLATEN-JAWA TENGAH - Handayani, Wiwandari; Rudiarto, Iwan; Yesiana, Reny (Universitas Negeri Semarang, 2014)
This paper aims to further comprehend characteristic and influential factors oflocal potential development in peri urban area of Klaten – Central Java. Simpledescriptive statistic was applied to process the data obtained from questionairegiven to 57 respondents. The respondent are owner of various kinds of smallmediumindustries located in the peri-urban Klaten. The result of the analysisindicates that the activity of most of local based small-medium industries in periurbanKlaten are still lead to the production -oriented activities. Accordingly,based on the respondents’ perception, capital, labourers, and raw materials arechosen as the influential factors to boost the development of their local basedactivities. They are very unlikely to consider technology and innovation that mayimportant to create a more market based products/market-oriented activities asthe influential factors that should be further developed. Therefore, there is a needof paradigm shift for these economic actors to be directed to a morecontemporary thought that put element of technology and innovation as importantand should be improved rather than keep the traditional thought that onlyconsider conventional production factors as the key succes factors to developsuch economic activities.